Tertiary Students’ Metacognitive Strategies in EFL Writing: A Longitudinal Study - Wijaya, Alberik Ryan Tendy; Teopilus, Susana; Cendra, Anastasia Nelladia (Journal of Education Reseach and Evaluation, 2025)
University students often encounter difficulties in academic writing in English due to the complexity of managing the writing process. Limited understanding and application of metacognitive strategies in various writing stages are among the main obstacles to producing high-quality texts. This study aims to conduct an in-depth and longitudinal analysis of the metacognitive strategies employed by students before, during, and after the academic writing process in English. A quantitative approach was adopted, using a descriptive survey method with a longitudinal design. The participants were 74 students from three different cohorts of an English Education program, observed over two to three semesters depending on their cohort. Data were collected through an adapted version of the LLMWSIME questionnaire contextualized to the study, and supplemented with secondary data such as student writing samples, classroom observations, and writing assignment scores. Descriptive statistics were used to calculate means, standard deviations, and percentages, while qualitative analysis was conducted to interpret contextual data. The results show a positive development in students’ use of metacognitive strategies across the three writing stages, with the highest achievement observed in the evaluation stage. However, improvement is still needed in the planning and execution stages. The study concludes that metacognitive strategies develop gradually and play a vital role in enhancing students’ academic writing quality. The findings imply the importance of integrating balanced metacognitive skill development into writing curricula to support students in becoming reflective and independent academic writers.